Nonlocal parabolic boundary-value problem - Matychuk, M. I. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
For a parabolic system with time-dependent coefficients, we construct its Green function and present the classical solution of a two-point problem with nonlocal boundary conditions given by differential polynomials.